A comparative study to determine strength of autopolymerizing acrylic resin and autopolymerizing composite resin influenced by temperature during polymerization: An In Vitro study - Anuj Chhabra; I V Rudraprasad; D B Nandeeshwar; C Nidhi (Wolters Kluwer Medknow Publications, 2017)
Aim: Temporary coverage of a prepared tooth is an important step during various stages of the fixed dental prosthesis. Provisional restorations should satisfy proper mechanical requirements to resist functional and nonfunctional loads. A few studies are carried out regarding the comparison of the effect of curing environment, air and water, on mechanical properties of autopolymerizing acrylic and composite resin. Hence, the aim of this study was to compare the transverse strength of autopolymerizing acrylic resin and autopolymerizing composite resin as influenced by the temperature of air and water during polymerization. Materials and Methods: Samples of autopolymerizing acrylic resin and composite resin were prepared by mixing as per manufacturer's instructions and were placed in a preformed stainless steel mold. The mold containing the material was placed under different controlled conditions of water temperature and air at room temperature. Polymerized samples were then tested for transverse strength using an Instron universal testing machine. Results: Alteration of curing condition during polymerization revealed a significant effect on the transverse strength. The transverse strength of acrylic resin specimens cured at 60°C and composite resin specimens cured at 80°C was highest. Polymerizing the resin in cold water at 10°C reduced the mechanical strength. Conclusions: Polymerization of the resin in hot water greatly increased its mechanical properties. The method of placing resin restoration in hot water during polymerization may be useful for improving the mechanical requirements and obtaining long-lasting performance.